2016
DOI: 10.1088/1742-5468/2016/09/093502
|View full text |Cite|
|
Sign up to set email alerts
|

Noise-induced transition in human reaction times

Abstract: The human reaction/response time can be defined as the time elapsed from the onset of stimulus presentation until a response occurs in many sensory and cognitive processes. A reaction time model based on Piéron’s law is investigated. The model shows a noise-induced transition in the moments of reaction time distributions due to the presence of strong additive noise. The model also demonstrates that reaction times do not follow fluctuation scaling between the mean and the variance but follow a generalized versi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…Other cases where a simple K − S relation is found are in surface roughness analysis (Isoda and Kawashima, 2013;Sharifi-viand et al, 2014). It is also worth mentioning the contributions in medical and biological fields; they pertain to fluctuation responses in the visual cortex (Medina and Diaz, 2016a, 2016c or ventricular fibrillation (Gonzalez-Gonzalez et al, 2013); an apparently comprehensive review about "biological and psychological aspects of the K-S can be found in Cain et al (2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other cases where a simple K − S relation is found are in surface roughness analysis (Isoda and Kawashima, 2013;Sharifi-viand et al, 2014). It is also worth mentioning the contributions in medical and biological fields; they pertain to fluctuation responses in the visual cortex (Medina and Diaz, 2016a, 2016c or ventricular fibrillation (Gonzalez-Gonzalez et al, 2013); an apparently comprehensive review about "biological and psychological aspects of the K-S can be found in Cain et al (2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Here, the additive noise becomes small at near-threshold conditions, ∀ I ∼ I 0 ⇒ ρ → 0; being stronger at marked supra-threshold conditions, ∀ I I 0 ⇒ ρ 1. Therefore, when we said 'strong additive noise', it should be said, 'weak additive noise' and vice versa across the entire text in [1]. There is a noised-induced transition and the transition zone is now found at ρ ≈ 2.…”
mentioning
confidence: 94%
“…Due to an error, the two limiting regimes of the theory were interchanged. We regret to inform the readers that equation (16) in [1], that describes the ratio of the additive to the multiplicative noise in human reaction times, is flawed. Here, we report the correct expression, and, accordingly the modified figures 2(b), 3, and 4.…”
mentioning
confidence: 99%
See 1 more Smart Citation